Worker well-being before and during the COVID-19 restrictions: A longitudinal study in the UK - Diane Pelly; Orla Doyle; Michael Daly; Liam Delaney (University College Dublin, UCD Centre for Economic Research, 2021)
The potential impact of COVID-19 restrictions on worker well-being is currently unknown. In this study we examine 15 well-being outcomes collected from 621 full-time workers assessed before (November, 2019 - February, 2020) and during (May-June, 2020) the COVID-19 pandemic. Fixed effects analyses are used to investigate how the COVID-19 restrictions and involuntary homeworking affect well-being and job performance. The majority of worker wellbeing measures are not adversely affected. Homeworkers feel more engaged and autonomous, experience fewer negative emotions and feel more connected to their organisations. However, these improvements come at the expense of reduced homelife satisfaction and job performance.
hdl:10197/11940
Keywords: J08; J24; I31; 330; COVID-19 restrictions; workers; homeworking; subjective well-being; productivity; mental health; job satisfaction; engagement